DIGITAL CLINICAL AND METRIC ASSESSMENT OF MARGINAL PERIODONTAL TISSUES - Владимр Маркович Корчемный; Елена Александровна Киселева; Ксения Сергеевна Киселева; Сергей Владимирович Черненко; Ольга Сергеевна Корчемная; Динар Минзагитович Гарафутдинов; Игорь Анатольевич Тё; Елена Александровна Тё; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Кира Борисовна Мозес; Яэль Центер (Medicina v Kuzbasse, 2023)
Orthodontic treatment of dental anomalies and deformities with removable and non-removable devices causes a negative impact on the organs and tissues of the oral cavity, characterized by deterioration of oral hygiene, increased intensity of dental caries, the appearance of new foci of enamel demineralization and the development of inflammation of periodontal tissues. Early diagnosis in patients with dental deformities is very important for secondary prevention, i.e. the use of methods aimed at stabilizing and stopping the development of the disease in its early stages.